2018
DOI: 10.1080/10826084.2018.1536716
|View full text |Cite
|
Sign up to set email alerts
|

A Stroop in the Hand is Worth Two on the Laptop: Superior Reliability of a Smartphone Based Alcohol Stroop in the Real World

Abstract: Background. Attentional bias (AB) is the tendency for substance-related stimuli to grab attention. The addiction Stroop task is widely used for measuring AB in the lab, but it has poor reliability and inconsistent predictive validity. Therefore, there is a need to improve the psychometric properties of the task. Objectives. This study contrasts the internal reliability and predictive validity of a basic (general alcohol words) and an upgraded (personalized alcohol pictures) Stroop task delivered in a neutral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Notably, no study to our knowledge has yet reported results for a mobile version of marijuana Stroop. In a mobile version of the alcohol Stroop, attentional bias scores were not associated with individual differences in drinking behavior [21]. In contrast, attentional bias for cigarette smoking cues assessed by a mobile version of the smoking Stroop administered on a personal digital assistant was associated with nicotine dependence severity [22] and nicotine craving during the early stages of a quit attempt [23].…”
Section: Mobile Cognitive Assessment Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Notably, no study to our knowledge has yet reported results for a mobile version of marijuana Stroop. In a mobile version of the alcohol Stroop, attentional bias scores were not associated with individual differences in drinking behavior [21]. In contrast, attentional bias for cigarette smoking cues assessed by a mobile version of the smoking Stroop administered on a personal digital assistant was associated with nicotine dependence severity [22] and nicotine craving during the early stages of a quit attempt [23].…”
Section: Mobile Cognitive Assessment Studiesmentioning
confidence: 85%
“…A computerized version of the marijuana Stroop task indicated that marijuana-related words captured the attention of marijuana-dependent individuals (ie, longer reaction time for marijuana-related words vs neutral words), but not healthy controls [12]. A mobile alcohol Stroop task had acceptable internal consistency reliability in real-world settings (Cronbach alpha=.70 to .74), with participants showing attentional bias to alcohol words [21].…”
Section: Mobile Phone Cognitive Tasks and Rating Of Distraction After Session Completionmentioning
confidence: 95%
See 1 more Smart Citation
“…46 À .89). Other studies have demonstrated different estimates of internal reliability (Robinson et al 2015;Spanakis et al 2019), however most do not report reliability despite its integral role in effect estimates and reproducibility (Baugh 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Alcohol-related AB, identified as a further potential driver of consumption (Field and Cox, 2008), has also generated inconsistent findings. On one hand, a bidirectional association between heightened AB and alcohol-seeking behaviours has garnered support (Field and Cox, 2008), and recent studies indicate that alcohol-related AB is most pronounced immediately prior to a drinking (Spanakis et al, 2019). However, the acute effects of alcohol on AB also appear to be affected by people's previous alcohol involvement and acute intoxication.…”
Section: Introductionmentioning
confidence: 99%